Synthesis and anti-inflammatory activities of novel dihydropyranoaurone derivatives - Wang, Zheng; Bae, Eun Ju; Han, Young Taek (Archives of pharmacal research, 2017)
A novel series of dihydropyranoaurone derivatives were synthesized and evaluated as potential anti-inflammatory agents. Late-stage derivatization by versatile piperazine-catalyzed aldol reaction between dihydropyanobenzofuran intermediate 2 and diverse aldehydes readily afforded the novel dihydropyranoaurone analogs. Evaluation of the synthesized dihydropyranoaurone derivatives and related compounds regarding their inhibiting inducible nitric oxide synthase and nitrite production of lipopolysaccaride-stimulated RAW 264.7 cells provided insight into the structure–activity relationship of aurone derivatives. Graphical abstract